Strategic Thinkers and Positioned Choices: Parental Decision Making in Urban School Choice. Issue 7 (November 2019) - Ellison, Scott; Aloe, Ariel M.
The economic logic of urban school reform holds that giving parents school choice options in an educational marketplace will lead to systemic improvements that will both resolve historical inequalities in American public schooling and will politically empower parents and urban communities. This article explores the economic logic of urban school reform policies that conceptualize parents as rational consumers of educational services and that seek normative justification for school choice as a mechanism to resolve educational inequalities and as a form of political empowerment. We do so through a qualitative research synthesis of five studies investigating the lived experiences of predominantly working-class parents of color as they navigate urban school choice. The findings from this synthesis suggest that the economic logic at work in the new politics of education obfuscates the complexity of the lived experiences of parents in urban communities. Parents hold nuanced views of urban school choice that reflect their positionality, report a limited or circumscribed form of empowerment, and express a preference for equitable learning opportunities in their locally zoned public schools.